Gas Kinetics, Rumen Characteristics, and In Vitro Degradability of Varied Levels of Dried and Fresh Cassava Leaf Top Fermented with Cassava Pulp - S. Morm; A. Lunpha; R. Pilajun; A. Cherdthong (Tropical Animal Science Journal, 2023)
The purpose of this study was to determine the impact of different levels of dried cassava leaf top (DCT) and fresh cassava leaf top (FCT) fermented with cassava pulp (CS) on the nutritional value of silage, gas kinetics, rumen characteristics, and in vitro degradability. Dietary treatments were administered using a completely randomized design (CRD) with eight treatments and three replicate runs. The eight treatments were as follows: 1) CS fermented no additive (nA), 2) CS fermented with additives (Saccharomyces cerevisiae, urea, molasses, and sugar) (CSA), 3) 95% CSA fermented with 5% DCT (5DCT), 4) 90% CSA fermented with 10% DCT (10DCT), 5) 85% CSA fermented with 15% DCT (15DCT), 6) 95% CSA fermented with 5% FCT (5FCT), 7) 90% CSA fermented with 10% FCT (10FCT), 8) 85% CSA fermented with 15% FCT (15FCT), respectively. After 21 days of fermentation, samples of the silages were taken for chemical analysis and utilized to examine the in vitro gas production and degradability. The results show that fermented CS with DCT at 5% to 10% DM had the highest increase in CP when compared to nA or CSA (p<0.05). In vitro dry matter disappearance (IVDMD) was significantly higher in CS fermented with 5% to 10% DCT (p<0.01), whereas CS fermented with FCT levels demonstrated lower IVDMD than the control group (p<0.01). The gas potential extent of gas production (p) and gas production from the insoluble fraction (b) did not differ significantly across treatments (p>0.05). However, the gas production from the immediately soluble fraction (a) was maximum when CS was fermented with 15DCT (p<0.05). Different treatments significantly affected the pH of the fermentation solution with the addition of 10DCT and 15DCT for 12 and 24 hours of incubation, respectively (p<0.01). After 12 hours of incubation, the population of protozoa was lowest when 5DCT and 10DCT were evaluated (p<0.01). In conclusion, CS fermented with DCT at a concentration of 5% to 10% can increase crude protein content, in vitro dry matter disappearance (IVDMD), and gas production from the immediately soluble fraction while decreasing the protozoa population.